YOUTUBE: A TEACHING MEDIA TO OPTIMIZE STUDENTS’ ENGLISH LISTENING COMPREHENSION SKILL - Lestari, Pratiwi; Leni Rohliah; Wirda Ningsih; Genta Ulina Hutagalung (Global Expert: Jurnal Bahasa dan Sastra, 2023)
Listening is one of important skills in English language learning since it provides input for the students. However, many students still encounter a lot of listening difficulties caused by various factors, one of which that should be urgently solved is the use of poor and restricted materials in the language teaching and learning. As the Information and Communication Technology (ICT) develops rapidly, educators should take the advantages of it. Educators can use teaching media that provide various kinds of listening materials and can be accessed online. One of the most popular media that is accessible anytime and anywhere is YouTube. This literature review article aims to describe the use of YouTube as a media to optimize students’ English listening comprehension skill. YouTube provides a wide variety of materials for teaching language. Educators and students can use some of many recommended YouTube channels, namely BBC News Review, TED Talks, and Easy English. They provide listening materials; news review, talks, and daily conversation which are very useful for the students to improve their listening comprehension as well as their communication skills. However, several things need considering when using YouTube in language teaching. Educators need to plan the activities and find materials that suit the students’ needs, interest, and level in order to optimize the teaching of listening so that at the end, the listening comprehension skill of the students can be optimized as well. In addition, it is highly suggested that educators invite parents to work together in guiding the students when doing individual learning.